1998
DOI: 10.1177/016555159802400606
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of self-citation across disciplines (1980-1989)

Abstract: The paper examines patterns of self-citation in six disciplines distributed equally among the physical and social sciences and the humanities. Sample articles were examined to determine the relative numbers and ages of self-citations and citations to others in the bibliographies and to the exposure given to each type of citation in the text of the articles. Significant differences in the number and age of citations between disciplines were found. Over all, 9% of all citations were self-citations; 15% of physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
2
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 9 publications
4
100
2
2
Order By: Relevance
“…Snyder and Bonzi (1998) reported it in the fields of Asian studies, Chemistry and Geology. Aksnes (2003) witnessed it in the publications by Norwegian authors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Snyder and Bonzi (1998) reported it in the fields of Asian studies, Chemistry and Geology. Aksnes (2003) witnessed it in the publications by Norwegian authors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tolisano, Song and Cable (2015) observed that the last researcher in the author list of collaborative works are more frequent self-citers and are more likely than lead authors to cite themselves. There are also a few studies which could not either find any relation, or observe negative correlation, between these two variables (Glanzel and Thijs 2004;Huston 2006;Shah, Gul and Gaur 2015;Snyder and Bonzi 1998;Tagliacozzo 1977). In Plant Physiology and Neurobiology, Tagliacozzo (1977) argued that the extent of self-citation did not appear to be related to the number of co-authors, and interpreted that when there is disparity in seniority among co-authors, the senior author provides most of the references, like a single author would provide in his/her publication.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Benzer bulgular birçok araştırmada da saptanmıştır (Karataş-Çetin ve Özer-Çaylan, 2015, Larivière, Sugimoto, ve Cronin, 2012Porter, 1980;Ramos-Rodriguez ve Ruiz-Navarro, 2004 Kendine atıf konusu uluslararası literatürde sıklıkla tartışılan konuların başında gelmektedir Al ve Soydal, 2012;Bonzi ve Snyder, 1991;Hyland, 2003;Schreiber, 2008;Snyder ve Bonzi, 1998). Bir alanın özel konularının (örneğin; Değerler Eğitimi Dergisi, Eğitimde Liderlik Dergisi gibi) yayımlandığı dergilerin kendine atıfların göreceli olarak alan veya genel konu dergilerine oranla daha yüksek çıkması olağan bir durumdur.…”
Section: Sonuç Ve Tartışmaunclassified
“…The second reason for high citation counts could be self-citation. In multi-authored articles, self-citation occurs when at least one author is common between the citing and the cited articles [59]. Thus, the more the number of authors per article, the higher is the probability of getting self-citations [56].…”
Section: Can Citation Be Associated With Collaboration?mentioning
confidence: 99%